Persepsi Masyarakat Terhadap Keberadaan Peternakan Ayam Broiler di Desa Cakura Kecamatan Polombangkeng Selatan Kabupaten Takalar - Sarmila Indah Putri; Asgaf, Khaifah; Muhammad Basir Paly (Universitas Islam Negeri Alauddin Makassar, 2025)
Broiler chicken farming is one of the rapidly growing agribusiness sectors that plays an important role in meeting the demand for animal protein. However, broiler farms located near residential areas may cause environmental impacts, such as unpleasant odors and waste pollution, which can affect the comfort of surrounding communities. This study aimed to analyze community perceptions of the environmental impacts caused by broiler chicken farming in Cakura Village, Polombangkeng Selatan District, Takalar Regency. This research employed a quantitative approach using a survey method. The population consisted of 160 residents living near broiler farms, and 61 respondents were selected as samples using the Slovin formula. Data were collected through observation, interviews, and questionnaires. The data were analyzed using descriptive quantitative analysis with a Likert scale to measure community perceptions regarding odor and waste impacts from broiler farming activities. The results showed that a significant portion of the community perceived disturbances caused by unpleasant odors originating from chicken manure and feed residues. In addition, farm waste was also considered a potential source of environmental pollution if not managed properly. Therefore, proper waste management and good sanitation practices in broiler farming are necessary to minimize environmental impacts and improve community acceptance of broiler farming activities.